Critical Success Factors for Technology Management in the Post Pandemic World - Blair, Garry; Morris, Michelle; Pagano, Rosane (Journal of UTEC Engineering Management, 2023)
DOI: https://doi.org/10.36344/utecem.2023.v01i01.011The requirement to achieve the successful implementation and operation of technology is more urgent than ever, given the changes to society imposed by the pandemic and post-pandemic events. The identification of critical factors for the success of technology has become paramount for organisations, irrespective of their sector. This paper accesses a literature review of current and seminal sources together with empirical research to discern a framework for examining the topic. A thematic analysis was performed to identify the key areas for critical project success factors. A summary of these areas for practice was then formulated, in order to assist both practitioners and academics in this sphere.Critical Success Factors (CSFs) in Technology Management are defined as the principal areas requiring satisfactory results in order to ensure the successful delivery of systems’ objectives. The use of ‘hard’, namely objective, and ‘soft’, namely subjective, information can be required to measure these factors. CSFs are also dynamic, in that they may change over time and thus require ongoing reflection and revaluation, to potentially redefine them in order to accommodate the organisation’s current environment.A semi-structured interview was held with an experienced project manager. The main themes were then discerned, using an inductive, grounded approach. The focus was on determining the critical factors for change management, as applied in this sphere.